History of Soviet School and Childhood in Personal Archives of Ural Teachers (1930-1980s) - E. V. Protasova (Научный диалог, 2018)
The subject area of the article relates to the interdisciplinary study of the history of Soviet school and childhood on the basis of personal archival funds of the Ural teachers. The relevance of the study is due to the weak study of sources of personal origin in the historical and local-territorial aspects. The publication recreates the objective conditions for the development of school education in the 1930-1980s in the Russian province. The main documents for the historical and pedagogical analysis were the materials of personal funds of V. A. Zanin and T. I. Khlypenko from the Berezniki Archive in Perm region. It is reported that both teachers during the Soviet period worked in Berezniki school № 1 named after A. S. Pushkin, which experience was advanced for a long time and deserved its studying by teachers of the Ural region. The article analyzes the memories of teachers and pupils, revealing the historical specifics of school and extracurricular educational practice. The experience of implementation of state projects in the field of education and upbringing is described. The data on the manifestation of pedagogical skills in the conditions of strengthening the role of a school for the development of the industrial Urals are given. The possibilities of archival funds for studying the life of children in the Russian province in the Soviet period are shown. The pedagogical ideas possessing axiological potential for the organization of modern educational practice are proposed.